PERILAKU STICKY COST DALAM KOMPENSASI EKSEKUTIF BANK BUMN DAN NON BUMN YANG TERDAFTAR DI BURSA EFEK INDONESIA - Luh Pande Eka Setiawati; Yura Karlinda Wiasa Putri (UNHI Press, 2021)
Knowing the difference in the level of sticky costs in executive compensation of BUMN and Non BUMN Banks is the purpose of this study, this study takes the period 2017-2019. Sticky cost is an unbalanced cost response when there is a change in activity. Executive compensation is the cost incurred for executives who perform performance-enhancing companies. The location of the research was conducted at the Indonesia Stock Exchange in the Banking Sector. The sampling technique used is non-probability sampling by purposive sampling. The type of data source used in this study is secondary data in the form of annual reports (annual reposts) of banking companies listed on the IDX for the 2017-2019 period. The data analysis technique used is multiple linear regression analysis. The results of the research obtained are proving that there is no difference in the level of sticky costs in executive compensation of state-owned banks and non-state-owned banks listed on the BEI.